ANALISIS SISTEM NON LINEAR MELALUI PENDEKATAN SISTEM LINEAR DENGAN PARAMETER BERUBAH-UBAH - widowati, widowati (MATEMATIKA, 2010)
This paper proposes  the relation between nonlinear systems with LPV systems (Linear  Parameter Varying  systems) where the non-linear systems can be described as LPV systems. Based  on the LPV systems description, the nonlinearity of the systems is represented by parameters  varying. Local properties of nonlinear systems are presented. It is assumed that all the conditions for the existence and uniqueness of solutions have been met. It is also assumed that the origin is a stationary point. Then, we will discuss how to analyze the stability of non-linear systems using the LPV systems approach. Furthermore, the bounds  of parameters to ensure the asymptotic stability of nonlinear systems  are given. To verify the proposed method, numerical simulations are demonstrated